2009
DOI: 10.1002/cncr.24291
|View full text |Cite
|
Sign up to set email alerts
|

Real‐time identification of liver cancers by using indocyanine green fluorescent imaging

Abstract: BACKGROUND: We have often encountered difficulties in identifying small liver cancers during surgery. Fluorescent imaging using indocyanine green (ICG) has the potential to detect liver cancers through the visualization of the disordered biliary excretion of ICG in cancer tissues and noncancerous liver tissues compressed by the tumor. METHODS: ICG had been intravenously injected for a routine liver function test in 37 patients with hepatocellular carcinoma (HCC) and 12 patients with metastasis of colorectal ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
687
5
7

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 743 publications
(757 citation statements)
references
References 28 publications
17
687
5
7
Order By: Relevance
“…ICG was prepared according to protocols used for abdominal surgery10; the dye was mixed with 10 ml sterile water, and 3·5 ml was injected intravenously. The injection could be repeated until a maximum dose of 5 mg per kg per day was reached.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…ICG was prepared according to protocols used for abdominal surgery10; the dye was mixed with 10 ml sterile water, and 3·5 ml was injected intravenously. The injection could be repeated until a maximum dose of 5 mg per kg per day was reached.…”
Section: Methodsmentioning
confidence: 99%
“…Initially used in the detection of macular degeneration8, the technique of angiography using indocyanine green (ICG) has been used to identify sentinel lymph nodes9, to determine the extent of oncological resections10 and to study hepatic function11. Recent studies have also demonstrated its usefulness in evaluating the vascular blood flow of intestinal anastomoses12.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, ICG angiography has been used to identify sentinel lymph nodes (37), determine the extent of oncologic resections (38), and study hepatic function (39). Recent studies have also demonstrated its usefulness in evaluating the vascular blood flow of intestinal anastomoses (40) and tissue flap reconstructions (41).…”
Section: Fluorescent Techniques With Icg In Neck Surgerymentioning
confidence: 99%
“…At our center, ICG for thyroid or parathyroid surgery is prepared according to the protocols used for abdominal surgery (38). Briefly, 25 mg ICG is mixed with 10 mL of sterile water (concentration, 2.5 mg/mL), and 3.5 mL is injected intravenously during the procedure by the anesthesia team.…”
Section: Fluorescent Techniques With Icg In Neck Surgerymentioning
confidence: 99%
“…ICG cannot escape the tight junctions of normal capillaries but extravasates from the leaky capillaries of tumors and becomes trapped in that tissue (23). Several groups have demonstrated in human patients that ICG can be used to detect hepatocellular carcinoma (HCC) and colorectal cancer liver metastases (24,25).…”
Section: Icg Imagingmentioning
confidence: 99%